PERANAN PPAT DALAM PENDAFTARAAN TANAH ULAYAT MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Dwikornida, Yevendri dan (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
Land has a very important meaning and role for human life, because everyone needs land during their life until they die and considering the structure of life and the economic pattern of the majority of which is still agrarian and as a country with an agrarian system, land is a very suitable and complex livelihood for each person to achieve prosperity in various fields, where the land itself is also the basic capital in the development of a nation and its benefits must be managed as well as possible including customary land, namely rights that are inherent as a special competence in customary law communities, in the form of authority/power to manage and regulate land and its contents with internal and external validity. In connection with the ownership of rights to customary land, UUPA regulates land registration which aims to provide legal certainty as regulated in Article 19 which reads,